2021
DOI: 10.3390/land10030280
|View full text |Cite
|
Sign up to set email alerts
|

Rural Districts and Business Agglomerations in Low-Density Business Environments. The Case of Extremadura (Spain)

Abstract: The strategy of the institutionalization and development of business agglomerations, in any of its analytical aspects (industrial district, local production system, cluster, etc.), has not had great results in Spanish regions with low business-density, probably due to the difficulty of finding an adequate implementation framework in administrative, geographic, and institutional terms. Based on the limitations presented by the identification methodologies of business agglomerations in low business-density terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…From each of these crises, the sector emerges restructured, sometimes without having overcome the previous crisis [92]. These processes coincide with the idea of the life cycle of the LPS, developed by Belussi and Sedita [93] and is identified in the LPS-IPTI [90,91].…”
Section: Institutionalmentioning
confidence: 85%
See 1 more Smart Citation
“…From each of these crises, the sector emerges restructured, sometimes without having overcome the previous crisis [92]. These processes coincide with the idea of the life cycle of the LPS, developed by Belussi and Sedita [93] and is identified in the LPS-IPTI [90,91].…”
Section: Institutionalmentioning
confidence: 85%
“…The changes that occurred in the agro-food industry in recent decades that affect the LPS-IPTI and the IPTI and shape them experience cycles of crisis and expansion [42,60,61,78,90,91]. From each of these crises, the sector emerges restructured, sometimes without having overcome the previous crisis [92].…”
Section: Institutionalmentioning
confidence: 99%
“…From each of these crises, the sector emerges restructured, sometimes without having overcome the previous crisis [92]. These processes coincide with the idea of the life cycle of the LPS, developed by Belussi and Sedita [93] and identified in the LPS-IPTI [90,91].…”
Section: Introductionmentioning
confidence: 82%
“…IPTIs present specific conditions that characterise the formation and continuity of LPS-IPTI (see Table 1). The changes that occurred in the agro-food industry in recent decades affect the LPS-IPTI and the IPTI that shape them experience cycles of crisis and expansion [42,60,61,78,90,91]. From each of these crises, the sector emerges restructured, sometimes without having overcome the previous crisis [92].…”
Section: Introductionmentioning
confidence: 99%
“…For example, [13] found that neighbourhood effects had a central role in determining where croplands expand, which led to agricultural expansion and landscape formation in Mato Grosso, Brazil. For the case of Spain, [14] found the presence of business agglomerations around rural areas in the Extremadura region. The authors propose that agglomeration economies be considered as an important element to explore endogenous development in low-density business environments.…”
Section: Exploratory Spatial Flow Data Analysismentioning
confidence: 99%